Does Public Country‐by‐Country Reporting Deter Tax Avoidance and Income Shifting? Evidence from the European Banking Industry. (2nd November 2020) - Joshi, Preetika; Outslay, Edmund; Persson, Anh; Shevlin, Terry; Venkat, Aruhn
ABSTRACT: In this study, we examine the effect of increased tax transparency on the tax planning behavior of European banks. In 2014, the European Union introduced public country‐by‐country reporting requirements to the banking industry. Treating this new requirement as an exogenous shock, we find limited evidence consistent with a decline in income shifting by the banks' financial affiliates in the post‐adoption period (starting from 2015). We do not, however, find robust evidence of a significant change in the consolidated book effective tax rates among the affected banks. Our findings suggest that increased transparency from public country‐by‐country reporting can deter tax‐motivated income shifting but that it did not appear to materially influence the banks' overall tax avoidance. Our findings have policy implications for the ongoing debate between the European Parliament, the Organisation for Economic Co‐operation and Development, and accounting standard‐setting bodies on whether to require multinationals to publish country‐by‐country reports. RÉSUMÉ: La déclaration publique pays par pays décourage‐t‐elle l'évasion fiscale et le transfert de revenus? Données issues de l'industrie bancaire européenne Dans cette étude, nous examinons l'effet d'une plus grande transparence financière sur le comportement en matière de planification financière des banques européennes. En 2014, l'Union européenne a imposé des exigences de déclaration publique pays par pays à l'industrie bancaire. En traitant cette nouvelle exigence comme un choc exogène, nous avons découvert peu de faits probants indiquant une réduction du transfert de revenus par les sociétés financières affiliées aux banques lors de la période suivant l'imposition de ces exigences (à compter de 2015). Toutefois, nous n'avons pas non plus découvert de preuves solides d'un changement important touchant les taux d'imposition réels consolidés parmi les banques touchées. Nos résultats portent à croire que la transparence accrue associée à la déclaration publique pays par pays peut décourager le transfert de revenus pour des raisons fiscales, mais ne semble pas influencer de façon marquée l'évitement fiscal global pratiqué par les banques. Nos résultats ont des conséquences sur le plan politique dans le cadre du débat en cours entre le Parlement européen, l'Organisation de coopération et de développement économiques et les organismes de normalisation comptable sur la pertinence d'obliger les multinationales à produire des déclarations pays par pays.